Examination of morphological and molecular changes in tomato (Solanum lycopersicum L.) seedlings with the application of tebuconazole - Halil İbrahim Öztürk; Hüseyin Bulut; Atilla Dursun (Acta Scientiarum Polonorum: Hortorum Cultus, 2022)
This study aims to determine the effects of tebuconazole substance used at different doses on the quality of tomato seedlings, retrotransposon mobility caused by this substance in the plants and its genotoxic effects and to determine the optimum dose to be used in practice in seedling production. Tebuconazole applied different concentrations (25, 50, 75, 100, 125 and 150 ppm) were tested. According to the study results, the seedling length and stem length significantly according to the applied doses. The study found out that the stem, leaf and root dry matter contents and leaf chlorophyll content (SPAD values) also statistically significantly changed based on the applied doses. According to the data obtained, the lowest seedling length (12.68 cm) and stem length (4.75 cm) were obtained from a dose of 150 ppm. The highest dry matter content in seedlings was obtained at a dose of 50 ppm in stem (22%) and at 0 ppm (control) in leaves (25.01%) and root. In the study, the highest leaf chlorophyll content (SPAD values) was determined at doses of 150 ppm, 125 ppm and 75 ppm, respectively. This study revealed that various doses of tebuconazole had a positive effect on controlling the height of tomato seedlings and specific quality characteristics of seedlings. In addition, molecular analyzes showed that polymorphism ratios in plants that were applied the substance at different doses varied between 4.70% and 38.09% and the GTS (genomic template stability) value varied between 61.91% and 95.30%. Analyses indicated that the polymorphism ratio increased depending on the increase in dose whereas the GTS value decreased.